2014
DOI: 10.1111/liv.12649
|View full text |Cite
|
Sign up to set email alerts
|

BCLC stage B hepatocellular carcinoma and transcatheter arterial chemoembolization: a 20‐year survey by the Italian Liver Cancer group

Abstract: In clinical practice, TACE cannot be considered the best approach for BCLC stage B patients who represent a heterogeneous population and are often suitable for more aggressive therapies, which lead to a better survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 37 publications
3
26
0
1
Order By: Relevance
“…As it is recently stated in a study from the Italian Liver Cancer Group in which TACE for BCLC-B was analysed on 405 patients, "TACE cannot be considered the best approach for BCLC stage B patients who represent a heterogeneous population and are often suitable for more aggressive therapies, which lead to a better survival". 24 An important matter of debate would be the impact that pretreatment biopsy could have for a biopsy-guided protocol. 22,25,26 It has been recently reported that biopsy for microvascular invasion is not as accurate as it should be.…”
Section: Discussionmentioning
confidence: 99%
“…As it is recently stated in a study from the Italian Liver Cancer Group in which TACE for BCLC-B was analysed on 405 patients, "TACE cannot be considered the best approach for BCLC stage B patients who represent a heterogeneous population and are often suitable for more aggressive therapies, which lead to a better survival". 24 An important matter of debate would be the impact that pretreatment biopsy could have for a biopsy-guided protocol. 22,25,26 It has been recently reported that biopsy for microvascular invasion is not as accurate as it should be.…”
Section: Discussionmentioning
confidence: 99%
“…A close relationship exists between the level of serum AFP and HCC recurrence/metastasis [38, 39]. AFP values have been considered a significant independent predictor of large/multifocal patients [40]. We presumed that a reduction in the AFP level after TACE might indicate the preoperative TACE had reduced tumor activity, which in turn might lead to better results in the following resection procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In this patient subgroup where overall survival (OS) often extends beyond 2 years [2], guidelines recommend trans-arterial chemoembolization (TACE) with the intent of prolonging OS by achieving local disease control [3]. …”
Section: Introductionmentioning
confidence: 99%